Opini Member Mengenai Personal Selling Sales Moka Pos dalam Memasarkan Produk - Olga Puspa Novilini; Riza Hernawati (Jurnal Riset Public Relations, 2021)
Abstract. Large companies application cash Moka POS is one of business competitors in the online. Moka POS system is the point of sales. The point of sales arranged to present information business. If a cafe, then output is menu and price. The output of cash application was sent digitally through sms to customers cellular phones. Moka POS through personal selling post, sell their products use of the executive marketers sales which aims to affect consumer to purchase. On Moka POS sometimes frequent mistake by sales or communication on the application cashier online itself. To the Moka POS give to briefing sales. However sales was not able to practice so they cannot give satisfaction for their customers, this can be seen in figure a customer complaint. The purpose of research to know a member opinion about salesmanship sales, negotiating, marketing sales relationship Moka POS heading in markets better for you products. A method of descriptive with the sampling method of who used in research is the total sampling. The sample collection as many as 95 visitors. Based on the research done, shows that a member opinion about salesmanship sales, negotiating, relationship marketing Moka POS heading in markets better for you products sales could be said to be good because any product Moka POS offer will be able to understand, the manner of serving salesmanship sales, negotiating, relationship marketing to consumer good so consumers business operators become a member of the application of these Moka POS. Abstrak. Perusahaan besar aplikasi kasir online yaitu Moka POS adalah salah satu pesaing bisnis dalam bidang online. Moka POS merupakan aplikasi sistem Point of Sales. Sistem Point of Sales diatur agar dapat menyajikan informasi usaha. Apabila pada sebuah kafe, maka output-nya adalah daftar menu dan harga. Output dari aplikasi kasir tersebut dikirimkan secara digital melalui SMS ke ponsel pelanggan. Moka POS melalui personal selling, memasarkan produknya menggunakan tenaga pemasar yaitu Sales Executive yang bertujuan untuk mempengaruhi konsumen agar melakukan pembelian. Pada Moka POS terkadang juga sering terjadi kesalahan komunikasi oleh sales ataupun pada aplikasi kasir online itu sendiri. Untuk meminimalis keluhan-keluhan tersebut, Moka POS memberikan pembekalan kepada sales. Namun ternyata sales tersebut belum mampu mempraktekannya sehingga mereka tidak dapat memberikan kepuasan bagi pelanggannya, hal ini dapat dilihat pada gambar keluhan pelanggan. Tujuan penelitian untuk mengetahui opini member mengenai salesmanship sales, negotiating, relationship marketing sales Moka POS dalam memasarkan produk. Metode deskriptif dengan sampling yang digunakan dalam penelitian adalah total sampling. Pengambilan sampel sebanyak 95 orang. Berdasarkan hasil penelitian, menunjukkan bahwa opini member mengenai salesmanship sales, negotiating, relationship marketing sales Moka POS dalam memasarkan produk bisa dikatakan baik karena setiap produk Moka POS yang di tawarkan dapat di mengerti, cara melayani salesmanship sales, negotiating, relationship marketing terhadap konsumen baik sehingga konsumen pelaku usaha menjadi member dari aplikasi Moka POS tersebut.